Can an Abusive Supervision Be a Predictor of Doocing? Comment on Akram, Z.; Li, Y.; Akram, U. When Employees Are Emotionally Exhausted Due to Abusive Supervision. A Conservation-of-Resources Perspective. Int. J. Environ. Res. Public Health 2019, 16, 3300 - Fantinelli, Stefania (Int J Environ Res Public Health, 2020)
Thanks to the research work of Akram and colleagues on the consequences of an abusive supervision, it is possible to hypothesize a new point of view of the doocing phenomenon. According to the authors, an abusive supervision can cause, through the interaction of some mediators and moderators, counterproductive work behaviors; this comment proposes that these behaviors can be performed also in an online context. As a consequence, a worker could be fired because of something posted on social media (doocing). Another relevant point of view concerns the great responsibility given to supervisors and management with regard to the care of job environment from an emotional point of view.